Student Evaluation of Teachers’ Effectiveness (SETE) scale: translation, cross-cultural adaptation and psychometric properties in a Latin American sample - Villar-Guevara, Miluska; Livia-Segovia, José Hector; García-Salirrosas, Elizabeth Emperatriz; Fernández-Mallma, Israel (Frontiers in Education, 2024)
Teacher effectiveness is a burgeoning field. Those responsible for educational policies seem increasingly committed to this fact, since it is one of the most important factors that influence the success of a university student; for this reason, the study of this topic has gained relevance in recent years. Therefore, an instrument with adequate psychometric properties is needed to measure this construct in Spanish-speaking countries.The study had the purpose of translating, adapting, and evaluating the internal structure, providing evidence of reliability and validity of the Student Evaluation of Teachers' Effectiveness (SETE) Scale in a Latin American sample.Methods: An instrumental study was carried out and through convenience sampling, data were collected from 1000 university students from South America belonging to a private educational network. The participants were between 18 and 40 years old (M= 21.25, SD= 2.99). Analyzes used Structural Equation Modeling (SEM) with AMOS 24 statistical software.Results: Confirmatory Factor Analysis provided a 4-factor, 28-item fit model (CMIN/DF= 4.359; CFI= 0.956; SRMR= 0.030; RMSEA= 0.058). The results demonstrated good internal consistency (α= between 0.927 and 0.961; CR= between 0.927 and 0.962; AVE= between 0.646 and 0.799). Evidence of validity and reliability was obtained for the total sample. Discussion: This adaptation and validation of the SETE scale makes it a valid, useful, reliable, and necessary tool that can be considered to evaluate teachers' effectiveness from the perspective of university students.